Pengaruh Good Corporate Governance Dan Budaya Organisasi Terhadap Pencegahan Fraud Pada PT Bank Central Asia Tbk - Purwatiningsih Lisdiono; Monica Salim; Suwarno Suwarno (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The Covid-19 pandemic has caused financial crises in almost all countries in the world. Based on the results of the ACFE survey, they found more forms of cheating during the pandemic. The banking industry has a very important role in supporting national economic development, for that it is important for banks to prevent fraud. If a bank fails to maintain credibility, it will have an impact on other similar banks and even the entire banking system, which in turn will reduce the financial stability of the country. The purpose of this study was to determine the effect of good corporate governance and organizational culture on fraud prevention at PT Bank Central Asia, Tbk. The author conducted research in three BCA Sub-Branch Offices, namely, Mayor Oking Citeureup, Pasar Cibinong and Graha Cibinong located in Bogor. This study used a sample of 42 respondents. The analytical method used to test the hypothesis is multiple linear regression processed with SPSS 25. The results show that good corporate governance has a positive effect on fraud prevention, organizational culture has a positive effect on fraud prevention, and good corporate governance and organizational culture simultaneously affect fraud prevention. Keywords: Good Corporate Governance, Organizational Culture and Fraud Prevention